COMMUNICATIVE LANGUAGE TEACHING IN SECONDARY EDUCATION: PRINCIPLES AND PRACTICE (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This paper examines the application of Communicative Language Teaching (CLT) in secondary school English classrooms, focusing on how it can foster communicative competence through authentic, learner-centered activities. It explores the theoretical foundation of CLT, outlines its key principles, and presents practical strategies for integrating all four language skills—speaking, listening, reading, and writing—into cohesive, task-based lessons. The findings suggest that CLT, when adapted to learners’ needs and contexts, can significantly improve language proficiency and learner motivation.